1997
DOI: 10.1002/(sici)1099-1034(199712)32:4<297::aid-gj736>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous subvolcanic activity on the Beara Peninsula, SW Ireland

Abstract: Magmatic activity associated with the Munster Basin has been more widespread than previously reported. The Munster Basin is a substantial sedimentary basin, and towards the end of its extensional phase of development, at the beginning of the Variscan orogeny in Ireland, numerous intrusions were emplaced into consolidated Upper Devonian and Lower Carboniferous sediments on the Beara Peninsula. One hundred and sixty-four sills and dykes have been mapped which are subalkaline to alkaline in nature. Two separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…14c). The origin of this anomaly is not understood but may be related to the persistence of igneous intrusions that outcrop in localized inliers at the south coast (Coe 1966; Avison 1984; Byrne & O'Dwyer 1994; Pracht & Kinnaird 1995, 1997; Readman et al 1997) and are also proposed to extend beneath the Munster Basin (Gardiner & Sheridan 1981). According to O'Connor & Brück (1978), these intrusions may have resulted from subduction processes.…”
Section: Discussion and Geological Implicationsmentioning
confidence: 99%
“…14c). The origin of this anomaly is not understood but may be related to the persistence of igneous intrusions that outcrop in localized inliers at the south coast (Coe 1966; Avison 1984; Byrne & O'Dwyer 1994; Pracht & Kinnaird 1995, 1997; Readman et al 1997) and are also proposed to extend beneath the Munster Basin (Gardiner & Sheridan 1981). According to O'Connor & Brück (1978), these intrusions may have resulted from subduction processes.…”
Section: Discussion and Geological Implicationsmentioning
confidence: 99%
“…Monogenetic volcanoes tend to have a simple magma conduit system and it is likely that the various subvolcanic intrusions present in the sequence made use of the same fractures and syn-volcanic faults, with their spatial distribution again controlled by these syn-volcanic faults. Further to this, some of these faults were possibly part of a longer-lived system related to the extensional tectonic regime, as is the case with subvolcanic alkaline intrusions in the Munster Basin, where alkaline magmatism was induced by lithospheric thinning controlled by pre-existing zones of weakness in the Caledonide crust (Pracht & Kinnaird 1998). The linear, north-northwest, and east-northeast trends of the thicker Knockroe Volcanic Formation intrusions on surface might mirror the orientations of such pre-existing zones of weakness/syn-volcanic faulting.…”
Section: Volcano-stratigraphical Setting Of the Pallas Green Depositmentioning
confidence: 95%
“…It is difficult to locate the destination of the K + released by the low-grade metamorphic fluids, but muscovite-rich trachyte sills investigated in the vicinity of the pipe (Fig. 1a) have undergone extensive sodic metasomatism (Pracht and Kinnaird, 1997;Brady, 2010). They are composed essentially of near endmember albite with a distinctive checkerboard texture that is indicative of albitization (Menge.…”
Section: Modification Of Primary Meltmentioning
confidence: 99%
“…A CARBONIFEROUS tuffisitic intrusion at Cahermore on the southern Beara Peninsula of southwest Ireland is one of a number of subvolcanic intrusions that have been reported to contain significant concentrations of carbonate, leading Coe (1969) to compare them with carbonatites. However, the carbonate-rich intrusions have not previously been fully described or their petrogenesis established due to their lowgrade regional metamorphic history (Pracht, 1994(Pracht, , 2000Pracht and Kinnaird 1997). Carbonate volcanism in other parts of western Europe, such as Calatrava, central Spain (Bailey et al, 2005;Humphreys et al, 2010) and the Limagne Basin, France (Bailey et al, 2006) has been shown to be derived directly from the mantle in eruption styles similar to those of kimberlites and other ultramafic magmas, and it characteristically contains chromite that is similar to that in kimberlites (Bailey et al, 2005(Bailey et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%